More stories please! a review of research into the use of literature as a means to improve emotional intelligence and learner performance in the ESL classroom - John Mark Storey (Pennwell Corporation, 2020)
While there is significant evidence to indicate that emotional intelligence is a major factor in second language learning, there is also an impressive body of research suggesting that EI can be inculcated through the close reading and analysis of emotion-inducing stories. On the basis of these findings, it would seem legitimate to try to maximise the potential for story use in the ESL classroom as a means to raise learners’ EQ and thus improve learner performance. This paper examines research into the role of stories in inculcating emotional Intelligence (principally empathy, motivation and Foreign Language Anxiety) and discusses the implications of these studies for ESL education.